Determinants of House Price Dynamics. What Can We Learn From Search Engine Data? - Lars Bennöhr; Marco Oestmann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
There is a broad literature about fundamental determinants of house prices, which received increasing attention in the aftermath of the subprime crisis. However, there might be several other partly unobservable socio-demographic, psychological or individual factors influencing real estate price dynamics. Using quarterly data, we try to capture such effects by including relevant Google search engine query information into a set of standard fundamental variables. We perform fixed-effects regressions for a panel of 14 EU-countries comprising the years 2005-2013. As dependent variable the house price index (HPI) from Eurostat is employed. We find that Google data as a single aggregate measure of unobserved variables plays a substantial role in explaining house price developments.
Keywords: C23; C82; R21; R31; 330; Google Trends; House Price Index; Real Estate; Google Econometrics